2016
DOI: 10.1080/2162402x.2016.1245267
|View full text |Cite
|
Sign up to set email alerts
|

The tumor microenvironment disarms CD8+ T lymphocyte function via a miR-26a-EZH2 axis

Abstract: One of the most important factors that limit the potency of CD8 C cytotoxic T lymphocyte (CTL) responses is the tumor microenvironment (TME). Here, we provide evidence that miR-26a is a negative regulator of CTL function in the TME. Specifically, we identified miR-26a as a crucial suppressor gene in CTLs from the TME, as we found that, miR-26a expression was elevated in CTLs to respond to TME secretome stimulation. CTLs from miR-26a-transgenic mice showed impaired IFNg and granzyme B production in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Inhibition of EZH2 in tumor-specific T cells increases the tumor burden and the metastatic potential in mice models of ovarian cancer [ 41 ]. Long et al identified that miR-26a expression is elevated in CTLs responding to tumor microenvironment secretome stimulation, miR-26a inhibits EZH2 to impair CTL function, indicating miR-26a-EZH2 axis as a novel target to improve the efficacy of CTL-based cancer immunotherapy [ 42 ].…”
Section: Action Modes Of Ezh2mentioning
confidence: 99%
“…Inhibition of EZH2 in tumor-specific T cells increases the tumor burden and the metastatic potential in mice models of ovarian cancer [ 41 ]. Long et al identified that miR-26a expression is elevated in CTLs responding to tumor microenvironment secretome stimulation, miR-26a inhibits EZH2 to impair CTL function, indicating miR-26a-EZH2 axis as a novel target to improve the efficacy of CTL-based cancer immunotherapy [ 42 ].…”
Section: Action Modes Of Ezh2mentioning
confidence: 99%
“…Using a similar model, in which T cells are cultured in lyophilized conditioned media from tumor cells, Long et al recapitulated the increase in microRNA-26 to corroborate Zhao et al's findings. However, they suggested that unknown soluble factors within the TME mediate the induction of inhibitory microRNA expression (32,33). Using a humanized ovarian cancer model, DZNep-treated T cells were unable to control tumor metastasis to the same extent as control counterparts (33); similarly, CD8+ T cells transduced with a microRNA-26 decoy reduced tumor growth rate in an adoptive transfer melanoma model (32).…”
Section: Regulation Of Cd8+ T Cells During Cancermentioning
confidence: 99%
“…Ezh2 is negatively affected by factors present in the tumor microenvironment (TME) as evidenced by the reduction of Ezh2 transcription when T cells were activated in the presence of lyophilized tumor supernatant ( 32 , 33 ). Notably, one study observed that human CD8+EZH2+ T cells did not express KLRG1, TIM-3, or CD57, suggesting that EZH2 is primarily expressed in cycling or activated cells, not in senescent or anergic cells ( 15 , 33 , 34 ).…”
Section: Regulation Of Cd8+ T Cells During Cancermentioning
confidence: 99%
See 2 more Smart Citations